2016
DOI: 10.1177/1049732315610522
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Child Body Size and Health Care Seeking for Undernourished Children in Southern Malawi

Abstract: Child undernutrition affects millions of children globally, but little is known about the ability of adults to detect different types of child undernutrition in low-income countries. We used focused ethnographic methods to understand how Malawian parents and grandparents describe the characteristics they use to identify good and poor child growth, their actual or preferred patterns of health seeking for undernourished children, and the perceived importance of child undernutrition symptoms in relation to other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 41 publications
(46 reference statements)
0
12
1
Order By: Relevance
“…Strikingly, despite the high proportion of undernutrition among children in our study sample, an overwhelmingly large number of mothers did not consider their children to be malnourished. Research from various settings has shown that parents’ (especially mothers’) perceptions of child undernutrition are likely to influence provision of care, and children’s overall growth and development are associated with households time spent in caring for children [39, 40]. However, mothers from poor households often lack appropriate information on aspects such as optimal feeding practices or need for extensive care during illnesses which are critical for addressing undernutrition [41, 42].…”
Section: Discussionmentioning
confidence: 99%
“…Strikingly, despite the high proportion of undernutrition among children in our study sample, an overwhelmingly large number of mothers did not consider their children to be malnourished. Research from various settings has shown that parents’ (especially mothers’) perceptions of child undernutrition are likely to influence provision of care, and children’s overall growth and development are associated with households time spent in caring for children [39, 40]. However, mothers from poor households often lack appropriate information on aspects such as optimal feeding practices or need for extensive care during illnesses which are critical for addressing undernutrition [41, 42].…”
Section: Discussionmentioning
confidence: 99%
“…Mothers who preferred an overweight silhouette for their child said that a larger size shows that the child is healthy and strong. Mothers who wanted their child to have a smaller body size (N = 28) listed foods similar to those who wanted their child to maintain or gain weight, such as porridge (54%); fruit, nsima and fizzy drinks (36%); sweetened yogurt (29%); meat and green leafy vegetables (25%); groundnuts (18%); and milk and rice (14%; was higher than in studies in Nigeria, Kenya, the Seychelles, South Africa, Tanzania and Zambia, some of which included both men and women or only overweight/obese adults (Akindele, Phillips, Igumbor, & Useh, 2017;Devanathan et al, 2013;Ettarh, Van de Vijver, Oti, & Kyobutungi, 2013;Muhihi et al, 2012;Tateyama et al, 2018;Yepes et al, 2015). In the present study, the percentage of women who correctly estimated their current size did not differ significantly by measured weight status, in contrast to some other studies, which found that overweight participants were more likely than normal weight participants to underestimate their weight status (Muhihi et al, 2012;Tateyama et al, 2018).…”
Section: Child Body Size Perceptions and Preferencesmentioning
confidence: 91%
“…However, the severity of malnutrition and the presence of co-morbid conditions have been shown to confer additional mortality risk among malnourished children [47]. Also delay in seeking healthcare [48] 6%). Majority (79.7%) of the patients spent a maximum of fourteen days on admission.…”
Section: Discussionmentioning
confidence: 99%